Pengaruh Electronic Word of Mouth, Fintech, dan Kualitas Produk terhadap Keputusan Pembelian (Emina Cosmetics) pada Generasi Z dengan Citra Merek sebagai Pemoderasi - Davhina Resta Mevia; Muhammad Junaid Kamaruddin (SAFE-Network, 2026)
This study aims to examine the influence of electronic word of mouth, fintech, and product quality on Generation Z’s purchasing decisions regarding Emina Cosmetics, with brand image serving as a moderating variable. The background of this study is based on the increasing number of online cosmetic transactions, leading Generation Z to increasingly rely on digital reviews, payment convenience (fintech), and product quality when making purchasing decisions. This study employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, analyzed using SmartPLS 4.0. Data were collected from 130 female Generation Z respondents including high school/vocational school students, college students, and the general public who use Emina Cosmetics products via a questionnaire. The results indicate that fintech and product quality have a positive and significant influence on purchasing decisions. Product quality is the primary consideration as it encompasses reliability, durability, and alignment with product specifications. Fintech also accelerates purchasing decisions by providing the convenience and speed of digital transactions. Brand image was found to have a positive and significant influence on purchasing decisions. Conversely, electronic word of mouth did not have a significant effect on purchasing decisions. Furthermore, brand image was unable to moderate the influence of electronic word of mouth, fintech, or product quality on purchasing decisions.